Analisis Pengaruh Kualitas Pelayanan Terhadap Loyalitas Konsumen di Rumah Makan Inibaru Rajanya Steak - Muzdalifa, Fera; , Drs. Agus muqorobin, MM (2015)
This research purpose was to analysis fifth dimension influence of service quality including tangible, reliability, responsive, assurance, and empathy by partially and also simultaneous have an effect on significant to consumer loyality of Inibaru Rajanya Steak Restaurant. Quantitative method was used in this research. Primery data in the form of questioner propagated direct to consumer pay a visit to minimize twice in restaurant. Research sample was taking by purposive sampling so get sample counted 100 respondents. Meanwhile, data was analyzed by using multiple linear regressions analyze. Based on the t test result have get tangible variable show that tangible have significant influence to consumers loyality with significant value 0,004 < 0,05; responsiveness varibel have significant influence to consumers loyality with significant value 0,005 < 0,05; reliability variable have significant influence to consumers loyality with significant value 0,003 < 0,0; assurance variabel have significant influence to consumers loyality with significant value 0,004 < 0,05; empathy variable have significant influence to consumers loyality with significant value 0,005 < 0,05 and fifth dimension influence of service quality including tangible, reliability, responsive, assurance, and empathy have simultaneous significant influence to consumers loyality of Inibaru Rajanya Steak Restaurant with significant value 0,000 < 0,05. Determination coefficient result (R2) known that Adjusted R square (R2) value counted 0,556, have means that variation change consumers loyality variable can explains by tangible, responsiveness, reliability, assurance, and empathy variable counted 55,6%. While the rest counted 44,4% can explains by the other varible outside research model.